Mechanical Properties of Sandwich Composites Reinforced by Nanoclays: An Overview - Parente, João (2020)
Structural sandwich composites have been widely used in many engineering applications, and this trend continues due to their superior mechanical properties, thermal insulation and acoustic damping. However, to further improve their mechanical properties, literature reports significant benefits obtained with nano-reinforcements. In this context, nanoclays are the most popular nano-reinforcements for polymeric nanocomposites, due to their relatively high ion exchange capacity, high aspect ratio and economic advantages. In order to stablish a systematic understanding for design criteria, this work intends to summarize all studies present in the open literature about this topic. It was possible to conclude that using nanoclays improves the mechanical properties of structural sandwich composites, especially in terms of impact strength. Nevertheless, the benefits obtained regarding fatigue performance are not adequately reported in the literature, revealing the need to develop these studies.